2021
DOI: 10.3390/biom11081187
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Biotinylated Spermine in Astrocytes: Effect of Cx43 siRNA, HIV-Tat Protein and Polyamine Transport Inhibitor on Polyamine Uptake

Abstract: Polyamines (PAs) are polycationic biomolecules containing multiple amino groups. Patients with HIV-associated neurocognitive disorder (HAND) have high concentrations of the polyamine N-acetylated spermine in their brain and cerebral spinal fluid (CSF) and have increased PA release from astrocytes. These effects are due to the exposure to HIV-Tat. In healthy adult brain, PAs are accumulated but not synthesized in astrocytes, suggesting that PAs must enter astrocytes to be N-acetylated and released. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 73 publications
(113 reference statements)
2
30
0
Order By: Relevance
“…Many studies have attempted to utilize polyamine blockade as antineoplastic therapy, in which robust anti-tumor results typically occur in combination with polyamine uptake inhibitors [ 23 , 65 , 66 ]. The explanation for the inclusion of polyamine uptake inhibitors in DFMO administration is because polyamines have a series of transporters dedicated to uptake in cells [ 67 ], which can rescue the effects of DFMO administration [ 68 , 69 ]. In neuroblastoma, recent work has shown that the combination treatment of polyamine uptake inhibitor and DFMO results in a dramatic reduction in tumor size in xenograft models [ 70 ], leading to the initiation of a number of clinical trials (ClinicalTrials.gov Identifiers: NCT02395666, NCT04301843, NCT02679144) and publications [ 71 , 72 ].…”
Section: The Role Of Polyamines In Cancer Immunosuppressionmentioning
confidence: 99%
“…Many studies have attempted to utilize polyamine blockade as antineoplastic therapy, in which robust anti-tumor results typically occur in combination with polyamine uptake inhibitors [ 23 , 65 , 66 ]. The explanation for the inclusion of polyamine uptake inhibitors in DFMO administration is because polyamines have a series of transporters dedicated to uptake in cells [ 67 ], which can rescue the effects of DFMO administration [ 68 , 69 ]. In neuroblastoma, recent work has shown that the combination treatment of polyamine uptake inhibitor and DFMO results in a dramatic reduction in tumor size in xenograft models [ 70 ], leading to the initiation of a number of clinical trials (ClinicalTrials.gov Identifiers: NCT02395666, NCT04301843, NCT02679144) and publications [ 71 , 72 ].…”
Section: The Role Of Polyamines In Cancer Immunosuppressionmentioning
confidence: 99%
“…Uptake system for all polyamines, putrescine (PUT), SPD, and SPM, are present in astrocytes (Dot et al, 2000(Dot et al, , 2002Malpica-Nieves et al, 2020. The accumulated polyamines can also be released from astrocytes through multiple pathways: astrocytic connexin Cx43 hemichannels (Cx43 HCs) (Skatchkov et al, 2010(Skatchkov et al, , 2014(Skatchkov et al, , 2016Kirichenko et al, 2021;Malpica-Nieves et al, 2021), vesicular uptake/release mechanisms (Soulet et al, 2004;Hiasa et al, 2014;Takeuchi et al, 2017;Zorec et al, 2018), or by reverse transport via polyamine transporters (Makarov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines have been suggested to either directly target AMPARs ( Rozov and Burnashev, 1999 ), Ca 2+ channels ( Herman et al, 1993 ; Ferchmin et al, 1995 ), NMDARs ( Benveniste and Mayer, 1993 ), Kir channels ( Lopatin et al, 1994 , 1995 ; Nichols and Lopatin, 1997 ; Skatchkov et al, 2000 , 2002 ; Kucheryavykh et al, 2007 , 2008 ), TRPV channels ( Ahern et al, 2006 ), Cx43 GJCs ( Skatchkov et al, 2015 ; Kucheryavykh et al, 2017 ), or ASIC channels ( Duan et al, 2011 ). Spermidine (SPD) protects from age-related alterations of synapses via autophagy mechanism ( Sigrist et al, 2014 ; Maglione et al, 2019 ), however, data on the release of polyamines from astrocytes with consequent effect on neighboring inhibitory interneurons were reported only in astrocyte culture ( Malpica-Nieves et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, PAs, such as Spm and Spd, are involved in glial-neuronal communication, are not synthesized, but are stored almost exclusively in glial cells [ 16 ], from which they can be released to regulate neuronal synaptic activity [ 44 , 45 ]. Organic cation transporters’ potential pathways allowing the transfer of PAs in and out of astrocytes [ 44 , 45 , 75 , 76 ]. The low level of Spm observed in astrocyte processes can be explained by hypothesizing that astrocytes are excreting Spm via connexins and/or organic cation transporters to replenish neurons depleted of Spm and keep a constant concentration of this molecule as well as the right Spm/Spd balance within neuronal cells.…”
Section: Reduced Spm Content In Reactive Astrocyte Processesmentioning
confidence: 99%